Clinicoanatomical substrates of selfish behaviour in amyotrophic lateral sclerosis – An observational cohort study. (January 2022) - Lulé, Dorothée; Michels, Sebastian; Finsel, Julia; Braak, Heiko; Del Tredici, Kelly; Strobel, Joachim; Beer, Ambros J.; Uttner, Ingo; Müller, Hans-Peter; Kassubek, Jan; Juengling, Freimut D.; Ludolph, Albert C.
Abstract: Objective: ALS primarily affects motor functions, but cognitive functions, including social understanding, may also be impaired. Von Economo neurons (VENs) are part of the neuronal substrate of social understanding and these cells are histopathologically altered in ALS. We investigated whether activity in areas including VENs is associated with an impairment of cognitive tasks that mirror social functioning. Methods: In this observational prospective study, ALS patients (N = 26) were tested for cognitive behavioural function, encompassing different aspects of empathetic understanding (interpersonal reactivity index, IRI), social behaviour (ultimatum game), recognition of faux-pas situations, and general cognitive functioning (Edinburgh Cognitive and Behavioural ALS Screen, ECAS). For in vivo pathological staging according to Braak, DTI-MRI was performed to determine those ALS patients with expected pathological involvement of VENs (B ALS stages 3 + 4) compared to those without (B ALS stages 1 + 2). Expected hypometabolism of cerebral areas was determined with 18 F-FDG PET in N = 20 ALS patients and compared to N = 20 matched healthy controls. Volume of interest analysis was performed in the anterior cingulate cortex (ACC) and the anterior insular cortex (AIC), which contain high numbers of VENs. Results: Compared to those without expected pathological involvement of VENs (B/B ALS stages 1 + 2), ALS patients with anticipated pathological involvement of VENs (B/B ALS stages 3 + 4) presented with significantly reduced fantasy to understand the mindset of others (IRI) and, social behaviour was more selfish (ultimatum game) despite the fact that cognitive understanding of socially inappropriate behaviour of others (faux-pas) was unimpaired. 18 F-FDG-PET showed hypometabolism in ACC and AIC in ALS patients with anticipated pathological involvement of VENs compared to those without and this was significantly correlated to cognitive-behavioral functions in certain tasks. Conclusion: Here, we present evidence of altered social behaviour in ALS patients associated with regional 18 FDG-PET hypometabolism in areas with a high density of VENs, thereby suggesting a possible causal association. Graphical abstract: Image 1